Clozapine prescription rates in Southeast Europe: A cross-sectional study - Manuela Russo; Manuela Russo; Dragana Ignjatovic-Ristic; Dan Cohen; Aliriza Arenliu; Stojan Bajraktarov; Alma Dzubur Kulenovic; Lidija Injac Stevovic; Nadja Maric; Antoni Novotni; Nikolina Jovanovic (Frontiers in Psychiatry, 2023)
IntroductionInternational reports indicate that clozapine is under prescribed. Yet, this has not been explored in Southeast European (SEE) countries. This cross-sectional study investigates clozapine prescription rates in a sample of 401 outpatients with psychosis from Bosnia and Herzegovina, Kosovo by United Nations resolution, North Macedonia, Montenegro and Serbia.MethodsDescriptive analysis was used to explore clozapine prescription rates; daily antipsychotic dosage was calculated and converted into olanzapine equivalents. Patients receiving clozapine were compared to those not receiving clozapine; next those that were on clozapine monotherapy were compared to those who were on clozapine polytherapy regime.ResultsIt was showed that clozapine was prescribed to 37.7% of patients (with cross-country variation: from 25% in North Macedonia to 43.8% in Montenegro), with average dose of 130.7 mg/daily. The majority of patients on clozapine (70.5%) were prescribed at least one more antipsychotic (the most frequent combination was with haloperidol).DiscussionOur findings suggested that clozapine prescription rate in SEE outpatients is higher than in Western Europe. The average dose is significantly below the optimal therapeutic dosage recommended by clinical guidelines, and clozapine polytherapy is common. This might indicate that clozapine is prescribed mainly for its sedative effect rather than antipsychotic. We hope that this finding will be taken up by relevant stakeholders to address this non-evidence-based practice.